Mice heterozygous for an osteogenesis imperfecta-linked MBTPS2 variant display a compromised subchondral osteocyte lacunocanalicular network associated with abnormal articular cartilage - Danyukova, Tatyana; Alimy, Assil-Ramin; Velho, Renata Voltolini; Yorgan, Timur A.; Di Lorenzo, Giorgia; von Kroge, Simon; Tidow, Henning; Wiegert, Simon; Hermans-Borgmeyer, Irm; Schinke, Thorsten; Rolvien, Tim; Pohl, Sandra (Bone, 2023)
Missense variants in the MBTPS2 gene, located on the X chromosome, have been associated with an X-linked recessive form of osteogenesis imperfecta (X-OI), an inherited bone dysplasia characterized by multiple and recurrent bone fractures, short stature, and various skeletal deformities in affected individuals. The role of site-2 protease, encoded by MBTPS2, and the molecular pathomechanism underlying the disease are to date elusive. This study is the first to report on the generation of two Mbtps2 mouse models, a knock-in mouse carrying one of the disease-causative MBTPS2 variants (N455S) and a Mbtps2 knock-out (ko) mouse. Because both loss-of-function variants lead to embryonic lethality in hemizygous male mutant mice, we performed a comprehensive skeletal analysis of heterozygous Mbtps2+/N455S and Mbtps2+/ko female mice. Both models displayed osteochondral abnormalities such as thinned subchondral bone, altered subchondral osteocyte interconnectivity as well as thickened articular cartilage with chondrocyte clustering, altogether resembling an early osteoarthritis (OA) phenotype. However, distant from the joints, no alterations in the bone mass and turnover could be detected in either of the mutant mice. Based on our findings we conclude that MBTPS2 haploinsufficiency results in early OA-like alterations in the articular cartilage and underlying subchondral bone, which likely precede the development of typical OI phenotype in bone. Our study provides first evidence for a potential role of site-2 protease for maintaining homeostasis of both bone and cartilage.